Management of novel ecosystems: are novel approaches required?. Issue 10 (1st December 2008) - Seastedt, Timothy R; Hobbs, Richard J; Suding, Katharine N
Abstract : Most ecosystems are now sufficiently altered in structure and function to qualify as novel systems, and this recognition should be the starting point for ecosystem management efforts. Under the emerging biogeochemical configurations, management activities are experiments, blurring the line between basic and applied research. Responses to specific management manipulations are context specific, influenced by the current status or structure of the system, and this necessitates reference areas for management or restoration activities. Attempts to return systems to within their historical range of biotic and abiotic characteristics and processes may not be possible, and management activities directed at removing undesirable features of novel ecosystems may perpetuate or create such ecosystems. Management actions should attempt to maintain genetic and species diversity and encourage the biogeochemical characteristics that favor desirable species. Few resources currently exist to support the addition of proactive measures and rigorous experimental designs to current management activities. The necessary changes will not occur without strong input from stakeholders and policy makers, so rapid information transfer and proactive research–management activities by the scientific community are needed.